Implikasi Pengembangan Wisata terhadap Peningkatan Ekonomi Masyarakat Lokal di Desa Bengkak, Wongsorejo, Banyuwangi - Populis, Mars Zanda Wulan; Rahmani, Nur Maulidah Dini; Aisyah, Ratna Dwi Nur; Wahyudi, Septi Andini Islamiyah; Bramayudha, Airlangga (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
This study is aimed at studying the application of the economic development of the population of Bengkak village. This study uses the method of quality research where in collecting data by means of observation and research directly to the society by way of in-depth interviews to dig data. The use of qualitative methods is grouped into 2 parts namely primary data and secondary data. Primary data is an interview to the community and sekundary data obtained from journals, e-books and previous literary works that correspond to the topic of discussion. The results of the research reveal that all these potential can be developed in a way that is of public concern. If people don't care, tourism won't work properly. However, there are a number of inhibitory factors, such as the lack of attention of the local community to the hygiene of the surroundings, which makes the tourist area polluted and unpleasant to see. The local government has been trying to revive the tourism that exists in Bengkak.